2006
DOI: 10.1002/chem.200500047
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Studies of Water‐Soluble Porphyrins with Protein Encapsulated in Bis(2‐ethylhexyl)sulfosuccinate (AOT) Reverse Micelles: Aggregation versus Complexation

Abstract: We have investigated the interaction of two water-soluble free-base porphyrins (negatively charged meso-tetrakis(p-sulfonatophenyl)porphyrin sodium salt (TSPP) and positively charged meso-tetrakis(N-methylpyridinium-4-yl)porphyrin (TMpyP)) with two drug-carrier proteins (human serum albumin (HSA) and beta-lactoglobulin (betaLG)) in bis(2-ethylhexyl)sulfosuccinate (AOT)/isooctane/water reverse micelles (RM) by using steady-state and transient-state fluorescence spectroscopy. TSPP exhibited a complex pattern of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 74 publications
2
18
0
Order By: Relevance
“…Apparently the band at longer wavelength was due to low emission from molecular aggregates. This is in agreement with similar changes observed for the systems based on TPPS in micelles [23]. The low emission band, red-shifted with respect to that for monomers, was assigned to the H-aggregates.…”
Section: Resultssupporting
confidence: 91%
“…Apparently the band at longer wavelength was due to low emission from molecular aggregates. This is in agreement with similar changes observed for the systems based on TPPS in micelles [23]. The low emission band, red-shifted with respect to that for monomers, was assigned to the H-aggregates.…”
Section: Resultssupporting
confidence: 91%
“…Moreover, under acidic conditions TSPP is prevalently present in solution as a zwitterion. This has proved to contribute decisively to the formation of highly ordered molecular aggregates of the porphyrin at relatively low [TSPP] induced by different polymeric templates [12][13][14] including albumins [11,15]. These aggregates of J-type are particularly interesting in view of their possible applications in nonlinear optics, nanometer-sized photoconductors, and light harvesting systems and contributed also for the relevance of the studies carried on at pH=2.…”
Section: Introductionmentioning
confidence: 99%
“…This band has been assigned either as an H-aggregate or to the splitting of the Soret band [17,58]. In the case of TPPS 4 porphyrin [29], similar behavior to the (OD) 3 TPPS 3 porphyrin is exhibited, that is, DR < 1.…”
Section: Characterization Of the Langmuir-schaefer Films And Porphyrimentioning
confidence: 89%
“…It was reported that the J-aggregation of the TPPS 4 could be promoted in the presence of template agents such as surfactants [14,16,17], proteins [18], dendrimers [19] and helical polyacetylene [20] and polysaccharide [21], as well as at different medium, as the air-water interface [22][23][24], and liquid-liquid interface [25].…”
Section: Introductionmentioning
confidence: 99%